Risk behaviours among substance use disorder treatment seekers with and without adult ADHD symptoms - Kaye, S.; Gilsenan, J.; Young, J.; Carruthers, Susan; Allsop, Steve; Degenhardt, L.; van de Glind, G.; van den Brink, W. (Elsevier Ireland Ltd, 2014)
Background: Impulsivity and consequent risk-taking are features of both Attention Deficit Hyperactivity Disorder (ADHD) and substance use disorder (SUD). To date there are no data on the impact of comorbid ADHD on the likelihood and frequency of risk-taking behaviour among individuals with SUD. The current study aimed to examine drug-related, sexual and driving-related risk behaviours in people seeking treatment for SUD with co-occurring symptoms of Attention Deficit Hyperactivity Disorder (ADHD), taking into account potential confounders. Methods: 489 Australian adult SUD treatment seekers were administered a structured interview assessing demographics, drug use and SUD treatment history, psychiatric history, self-reported adult ADHD symptoms and self-reported drug-related, sexual and driving-related risk behaviours. Results: Almost a third (32%) screened positive for adult ADHD symptoms with onset prior to age 12. Those screening positive were more likely to report early onset (<15 years) nicotine and illicit drug use and to have a prior diagnosis of childhood ADHD, anxiety, depression and personality disorder. ADHD symptom status was not independently associated with injecting drug use-related or sexual risk-taking in the preceding month, but was an independent predictor of a greater overall number of driving offences, a higher frequency of driving without a seatbelt, a greater likelihood of having driven without a valid licence, more at-fault accidents and having one's licence disqualified at the time of interview. Conclusions: These findings suggest that the risk-taking behaviour that is common among people with SUD is further increased among those with comorbid ADHD symptoms, particularly with respect to dangerous driving practices.